Characteristics of Tc-MEP Waveforms for Different Locations of Intradural Extramedullary Tumors: A Prospective Multicenter Study of the Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Issue 2 (15th January 2022) - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Yoshida, Go; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Shigematsu, Hideki; et al.
Abstract : Study Design: Prospective multicenter study. Objective: To examine transcranial motor-evoked potential (Tc-MEP) waveforms in intraoperative neurophysiological monitoring in surgery for intradural extramedullary (IDEM) tumors, focused on the characteristics for cervical, thoracic, and conus lesions. Summary of Background Data: IDEM tumors are normally curable after resection, but neurological deterioration may occur after surgery. Intraoperative neurophysiological monitoring using Tc-MEPs during surgery is important for timely detection of possible neurological injury. Methods: The subjects were 233 patients with IDEM tumors treated surgically with Tc-MEP monitoring at 9 centers. The alarm threshold was ≥70% waveform deterioration from baseline. A case with a Tc-MEP alert that normalized and had no new motor deficits postoperatively was defined as a rescue case. A deterioration of manual muscle test score ≥1 compared to the preoperative value was defined as postoperative worsening of motor status. Results: The 233 patients (92 males, 39%) had a mean age of 58.1 ± 18.1 years, and 185 (79%), 46 (20%), and 2 (1%) had schwannoma, meningioma, and neurofibroma. These lesions had cervical (C1–7), thoracic (Th1–10), and conus (Th11-L2) locations in 82 (35%), 96 (41%), and 55 (24%) cases. There were no significant differences in preoperative motor deficit among the lesion levels. Thoracic lesions had a significantly higher rate of poor baseline waveform derivation (0% cervical, 6% thoracic, 0% conus, P  < 0.05) and significantly more frequent intraoperative alarms (20%, 31%, 15%, P  < 0.05). Use of Tc-MEPs for predicting neurological deficits after IDEM surgery had sensitivity of 87% and specificity of 89%; however, the positive predictive value was low. Conclusion: Poor derivation of waveforms, appearance of alarms, and worse final waveforms were all significantly more frequent for thoracic lesions. Thus, amplification of the waveform amplitude, using multimodal monitoring, and more appropriate interventions after an alarm may be particularly important in surgery for thoracic IDEM tumors. Level of Evidence: 3 Abstract : A study of Tc-MEP waveform monitoring during surgery for IDEM tumors with cervical, thoracic and conus locations showed poor baseline waveform derivation and more alarm cases indicating potential neurological injury for thoracic lesions. Thus, amplification of waveforms and better post-alarm interventions may be needed in surgery for thoracic IDEM tumors.